Experimental and Modeling Studies on the Prediction of Gas Hydrate Formation. (19th March 2015) - Liu, Jian-Yi; Zhang, Jing; Liu, Yan-Li; Tan, Xiao-Hua; Zhang, Jie
Abstract : On the base of some kinetics model analysis and kinetic observation of hydrate formation process, a new prediction model of gas hydrate formation is proposed. The analysis of the present model shows that the formation of gas hydrate not only relevant with gas composition and free water content but also relevant with temperature and pressure. Through contrast experiment, the predicted result of the new prediction method of gas hydrate crystallization kinetics is close to measured result, it means that the prediction method can reflect the hydrate crystallization accurately.